The Influence of Organizational Culture, Islamic Leadership, Islamic Work Ethic on Organizational Commitment of Employee at Nahdlatul Ulama University Surabaya With Job Satisfaction as a Mediating Variabel - Tatik Suryani; Reno Triyono (Jurnal Bisnis dan Keuangan, 2022)
This study examines four factors that are suspected to be causally influential on organizational commitment of Nahdlatul Ulama University employees, Surabaya. The purpose of this study was to determine whether or not there was an influence of organizational culture, Islamic Leadership and Islamic Work Ethic on organizational commitment of the employees of Nahdlatul Ulama University, Surabaya. with job satisfaction as a mediating variable. The population of this study was all employees of the University of Nahdlatul Ulama, Surabaya, which consisted of 227 lecturers and 135 education staff and was determined to be the sample with the formula from green as many as 122 people. Data collection used a questionnaire consisting of 69 questions which were previously tested for validity and reliability. The data analysis technique in this study used Partial least squares (PLS). The results showed that organizational culture, Islamic Leadership, Islamic Work Ethic had a direct and significant positive effect on organizational commitment. organizational culture and Islamic Leadership have a direct and significant positive effect on job satisfaction as well. however, Islamic Works Ethic has an effect on job satisfaction but not significantly. Job satisfaction mediates the relationship between organizational culture and Islamic learning on organizational commitment. Job satisfaction does not mediate the effect of the relationship between Islamic work ethics on organizational commitment.